Media Construction in Mining Issues in East Kalimantan - Jaka Farih Agustian; Andria Saptyasari; Silviana Purwanti (ETTISAL : Journal of Communication, 2026)
This study aims to analyze how media construct and frame mining issues, and how the relationship between power and knowledge plays a role in that process. Using Michel Foucault’s theory of power/knowledge, this paper offers a critical framework to understand how media shape public knowledge about mining and how power operates through media to direct discourse around the mining industry. Foucault’s concept of power and knowledge contributes to a new way of understanding social realities in modern society—where power is no longer viewed solely as repressive or authoritarian, but as something productive, dispersed, and embedded within social structures and interactions. In this context, media construction of mining issues is not merely about objective information delivery, but is shaped through social processes and power relations. Knowledge is produced through the interaction of media, government, and mining companies, often by highlighting the perceived benefits of mining activities. However, local media with pro-community perspectives can also expose the environmental and social risks of mining operations. In contemporary society, environmental issues must be critically examined through the lens of Foucault’s theory of power/knowledge,as environmental damage carries profound implications for social change. Thus, this study emphasizes the importance of a more holistic and critical approach in analyzing how media contribute to the construction of environmental discourse in the context of mining.